Разработка фотохимического метода разделения изотопов углерода; Известия вузов. Физика; Т. 53, № 11 - Мышкин В. Ф. Вячеслав Фёдорович; Хромяк М. И. Михаил Иванович; Беспала Е. В. Евгений Владимирович; Ленский В. Н. Владимир Николаевич (2010, 2010)
Заглавие с экрана